The Thervingian Gothic Uprising and the Obscure Battle of Marcianople (Early AD 377):: Research Problems and Basic Observations - LEVENIOTIS, Georgios; KALAFIKIS, Georgios (Byzantina Symmeikta, 2024)
The article points out and comments on some research questions regarding the opening stages of the AD 377–382 (not 376-382, as it is usually claimed) Gothic War, namely the Gothic entrance and subsequent revolt in Late Roman Thrace, as well as the so-called Battle of Marcianople that followed immediately after. Although this latter conflict has not been the subject of a specialized study until now, in our opinion, it bears significant historical importance for a variety of reasons: first, it was the first major armed conflict won by irregular Gothic warriors against the regular Roman army in decades; moreover, it led to the destruction of the Roman army of Thrace by the Thervingi Goths; finally, it constituted the prelude to the so-called “great disaster” or alternatively the “lamentable war”, namely the momentous Battle of Adrianople in August AD 378, with far-reaching implications for the integrity and fate of the Late Roman Empire.